A preliminary study on bees (Hemenoptera: Apoidea: Apiformes) from Northern and North central Vietnam - Long, Khuat Dang; Hue, Le Xuan; Hoa, Dang Thi; Phong, Pham Huy (Academia Journal of Biology, 2013)
For the first time, a list of tropical bee species found in Northern and North Central Vietnam is provided. This list includes 59 bee species in 21 genera belonging to 5 families. Bees were collected in protected areas, i.e. national parks and nature reserves in 2011-2012 during the spring-summer and summer-autumn seasons. At high elevations exceeding 300 m a.s.l., bee abundance was dominated by bumble bee species, such as Bombus magrettii and B. trifasciatus, and two honey bees Apis laboriosa and A. dorsata were occurred in forest and moutain areas. In abandoned orchards and fruit gardens close to forest fragments, bee abundance was dominated by Xylocopa species. In Northern and North Central Vietnam, deforested areas or cultivated lowlands were dominated by several bees having widespread distribution, namely native honey bee Apis cerana subspecies indica mainly of bred colonies, blue banded bees Amegilla albigena, A. zonata, leafcutter bee Megachile fulvovestila and carpenter bee Xylocopa tranquebararorum. In this paper notes on conservation status of bee, their behaviour and distribution are also discussed.